Effect of body mass index on maternal morbidity following peripartum hysterectomy - Wortman, A. C.; Hernandez, J. S.; Holcomb, D. S.; Wilson, K. L.; McIntire, D. D.; Sheffield, J. S. (Clinical obesity, 2015)
Summary The objective of this study was to estimate the impact of maternal body mass index (BMI) on maternal morbidity following unscheduled peripartum hysterectomy. A retrospective cohort study of consecutive peripartum hysterectomies at our institution from 1988 through 2012; scheduled hysterectomies were excluded. Medical records were reviewed and maternal, foetal and surgical data collected for each subject. Maternal BMI was categorized by the National Institute of Health classifications for overweight and obese. Statistical analyses included evaluation for trend. A total of 360 774 women delivered at Parkland Hospital during the study period with 665 (1.8 per 1000 deliveries) unscheduled peripartum hysterectomies performed. BMI was available for 635 women. Gestational diabetes, chronic hypertension and pregnancy‐related hypertension were significantly higher in all three obesity categories, P = < 0.01. Post‐partum complications, such as venous thrombosis and composite surgical morbidity did not differ among BMI groups. Estimated blood loss and units transfused did not differ across the BMI categories, P = 0.42 and P = 0.38, respectively. Increasing BMI was associated with longer surgical times and more wound infections, P = 0.01. These complications should be considered when approaching a peripartum hysterectomy in patients with obesity.